Electropolishing of Stainless Steel Implants for Stable Functional Osteosynthesis - Omelchuk, A.A.; Yudenkova, I.N.; Zakharchenko, M.F.; Bliznyuk, A.V. (Science and Innovation, 2024)
A new method for the electrochemical polishing (ECP) of stainless steel to be used for stable functional osteosynthesis has been developed. Implants have been polished in solutions based on trinary system H2SO4–H3PO4–H2O with a stepwise decrease in current density and increase in orthophosphoric acid concentration. The optimal polishing conditions (current density, solution composition, temperature and duration) have been determined. The developed method improves the quality and the mechanical properties of the surface polished.